Style and Accuracy in Writing - Dorothy Sparer (Journal of Applied Communications, 1981)
I'd like to start by focusing on some style bloopers which seem to show up on my desk, and probably yours, so often that I feel compelled to stand here and enlist your help in stamping them out.